2013
DOI: 10.1128/ec.00363-12
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Nannochloropsis gaditana to Nitrogen Starvation Includes De Novo Biosynthesis of Triacylglycerols, a Decrease of Chloroplast Galactolipids, and Reorganization of the Photosynthetic Apparatus

Abstract: Microalgae of the genus Nannochloropsis are capable of accumulating triacylglycerols (TAGs) when exposed to nutrient limitation (in particular, nitrogen [N]) and are therefore considered promising organisms for biodiesel production. Here, after nitrogen removal from the medium, Nannochloropsis gaditana cells showed extensive triacylglycerol accumulation (38% TAG on a dry weight basis). Triacylglycerols accumulated during N deprivation harbored signatures, indicating that they mainly stemmed from freshly synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

39
281
6
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 324 publications
(328 citation statements)
references
References 61 publications
39
281
6
2
Order By: Relevance
“…Nevertheless, the decrease in the other lipid classes is not equivalent to the increase in the content of the neutral lipids. This observation implies that, aside from the rearrangement of some polar lipids to form neutral lipids, de novo fatty acid synthesis is also induced (Martin et al, 2014;Simionato et al, 2013).…”
Section: Nannochloropsis Epa and Nutrient Limitationmentioning
confidence: 93%
See 2 more Smart Citations
“…Nevertheless, the decrease in the other lipid classes is not equivalent to the increase in the content of the neutral lipids. This observation implies that, aside from the rearrangement of some polar lipids to form neutral lipids, de novo fatty acid synthesis is also induced (Martin et al, 2014;Simionato et al, 2013).…”
Section: Nannochloropsis Epa and Nutrient Limitationmentioning
confidence: 93%
“…Most of these neutral lipids are triacylglycerides (TAGs); however, there are notable decreases in the other lipid classes (Martin et al, 2014;Simionato et al, 2013). Nevertheless, the decrease in the other lipid classes is not equivalent to the increase in the content of the neutral lipids.…”
Section: Nannochloropsis Epa and Nutrient Limitationmentioning
confidence: 95%
See 1 more Smart Citation
“…Until recently, studies of nutrient limitation in microalgae have focused on the effects seen one to several days after deprivation (Wykoff et al, 1998;Moseley et al, 2002;Urzica et al, 2013) when oil accumulation rates are high Li et al, 2010;Miller et al, 2010;Philipps et al, 2012;Simionato et al, 2013;Yang et al, 2013) and photosynthetic functions are already substantially diminished. Here, we focus on the induction phase to investigate the transition into a nutrient-deprived, oil-accumulating state and the regulation of photosynthesis during that transition.…”
mentioning
confidence: 99%
“…Photosynthetic yields decrease during N deprivation, even under phototrophic conditions where cells are entirely dependent upon photosynthesis (Philipps et al, 2012;Simionato et al, 2013). Chlorophyll (Chl) fluorescence, which is sensitive to environmental changes and stress conditions that induce alterations in photosynthetic components (Iwai et al, 2008), can monitor the efficiency of linear electron flow (Baker et al, 2007) and has indicated that in N. oceanica (Simionato et al, 2013) and other algae, including C. reinhardtii (Berges et al, 1996;Li et al, 2010;Blaby et al, 2013), photosynthetic efficiency falls after N deprivation. Photosynthetically driven metabolic fluxes can also be probed by supplying 13 C-labeled bicarbonate/CO 2 and quantifying 13 C incorporation into metabolite pools (Shastri and Morgan, 2007;Feng et al, 2010;Young et al, 2011).…”
mentioning
confidence: 99%